Report on the second Intracranial Hypertension Research Foundation conference - Tanne Emanuel (Cerebrospinal Fluid Research, 2008)
Abstract This report highlights a conference designed for patient education on elevated cerebrospinal fluid (CSF) pressure. The conference centered on chronic intracranial hypertension (IH) including the latest research and clinical information. It was sponsored by the Intracranial Hypertension Research Foundation and held at the University of Texas Medical School, Houston, on June 21–22nd, 2008.